(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The aim of this work was to simulate a severe accident at a typical PWR, initiated with a break in Emergency Core Cooling System line of a hot leg, using the MELCOR code. The model of this typical PWR was elaborated by the Global Research for Safety and provided to the CNEN for independent analysis of the severe accidents at Angra 2, which is similar to this typical PWR. Although both of them are not identical, the results obtained of that typical PWR may be valuable because of the lack of officially published simulation of severe accident at Angra 2. Relevant parameters such as pressure, temperature and water level in various control volumes, after the break at the hot leg, were calculated as well as degree of core degradation and hydrogen production within the containment. The result obtained in this work could be considered satisfactory in the sense that the physical phenomena reproduced by the simulation were in general very reasonable, and most of the events occurred within acceptable time intervals. However, the uncertainty analysis was not carried out in this work. Furthermore, this scenario could be used as a base for the study of the effectiveness of some preventive or/and mitigating measures of Severe Accident Management by implementing each measure in this model.